BALANCE BETWEEN LAW ENFORCEMENT AND SOCIAL PROTECTION IN DRUG ABUSE CRIMES (STUDY AT LABUHANBATU RESORT POLICE) - Delima Nasution; Henry Aspan; T Riza Zarzani (PT. Sinergi Legal Publisher, 2024)
Narcotics crime is a serious issue with widespread impacts on society. In Indonesia, despite the existence of Law No. 35 of 2009 on Narcotics, law enforcement against drug abusers and addicts still faces various challenges, including the imbalance between imprisonment and rehabilitation. The majority of narcotics cases result in imprisonment, even though the law mandates rehabilitation, indicating a disparity in legal application. This study employs a normative legal approach to analyze the law enforcement mechanisms in Labuhanbatu Regency, focusing on the balance between law enforcement and legal protection for drug abusers. The study's findings indicate that despite comprehensive law enforcement efforts, including legal actions, medical and social rehabilitation, and strict supervision of the investigative process, imprisonment remains dominant in practice. This balance is achieved through the integration of deterrence theory, Community Policing, and human rights, emphasizing the importance of rehabilitation and social reintegration for drug abusers. In conclusion, to achieve fair and proportional legal protection, there is a need for reform in legal application, with a greater focus on rehabilitation over imprisonment, as well as the enhancement of the integrity and professionalism of law enforcement officers.